2020
DOI: 10.13106/jafeb.2020.vol7.no2.107
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Ownership Structure on Systemic Risk of Listed Companies in Vietnam

Abstract: The research objective of the paper is to clarify the factors influencing system risks of listed companies in Vietnam, with a focus on clarifying the relationship and quantifying the impacts of ownership structure on systemic risk of listed companies. The data used in this study included financial statements and stock price data of listed companies on the Ho Chi Minh City Stock Exchange and Hanoi Stock Exchange of Vietnam stock market in the period from 2010 to 2017. The paper used the method of estimation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…Results of previous studies show that a capital investment/contribution relationship often goes beyond financial contributions and extends to training, management transfer, and technical cooperation. A number of studies in different countries also show a positive relation between the foreign ownership ratio and financial performance of firms such as Olga ( 2009), Chibber and Majumdar (1999), Douma et al (2006), Vu et al (2019), Nguyen and Dang (2017). In contrast to the above studies, some authors such as Xu and Wang (1999), Lee (2008), Abbas et al (2009), and Nguyen (2018) found no indication that foreign ownership ratio was correlated with financial performance of firms.…”
Section: Foreign Ownership Ratiomentioning
confidence: 98%
See 1 more Smart Citation
“…Results of previous studies show that a capital investment/contribution relationship often goes beyond financial contributions and extends to training, management transfer, and technical cooperation. A number of studies in different countries also show a positive relation between the foreign ownership ratio and financial performance of firms such as Olga ( 2009), Chibber and Majumdar (1999), Douma et al (2006), Vu et al (2019), Nguyen and Dang (2017). In contrast to the above studies, some authors such as Xu and Wang (1999), Lee (2008), Abbas et al (2009), and Nguyen (2018) found no indication that foreign ownership ratio was correlated with financial performance of firms.…”
Section: Foreign Ownership Ratiomentioning
confidence: 98%
“…When studying Vietnamese firms with the main research methods as Pooled OLS, FEM, REM, or GMM, many authors found evidence of the positive correlation between these factors. For example, Vu et al (2019), Nguyen and Dang (2017), Dinh and Ho (2017), Nguyen and Pham (2017) showed that foreign ownership in Vietnam has positive impact on financial performance at the significance level of 1%-5%. This positive correlation was explained by the authors based on the advantages that foreign investors bring to firms.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The concept of corporate Governance has been transformed into the term of corporate management research previous period (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010). The author suggests that firms need to severely c implement governance, to reduce the agency cost and to increase performance (VU et al, 2020). The author has analyzed the effect of corporate governance on the firm's financial performance (Shahar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kim and Lu (2011) show that the relation between managerial ownership and firm value depends on the strength of external governance. Aggarwal, Erel, Ferreira and Matos (2011) find that international institution investment improves firm value (see also Vu, Phan and Dang, 2020 on Vietnamese sample). Faccio and Lasfer (1999) find no relations on the U.K. sample and attribute their findings to the fact that U.K. provide stronger outside governance mechanisms than the U.S.…”
Section: Introductionmentioning
confidence: 90%